The relationship between Type D personality with atherosclerotic plaque and cardiovascular events: The mediation effect of inflammation and kynurenine/tryptophan metabolism - Wang, Yini; Liu, Guojie; Zhao, Zhenjuan; Li, Ling; Yin, Shi; Sun, Xiao; Yu, Bo; Gao, Xueqin; Lin, Ping; Yang, Yanjie (Frontiers in Cardiovascular Medicine, 2022)
Purpose: Type D personality is associated with coronary plaque vulnerability and cardiovascular events. However, the underlying mechanism has not been elucidated. In this study, we determined whether inflammatory status in plasma, in combination with kynurenine pathway activity in Type D individuals, is associated with plaque vulnerability and cardiovascular events in patients with coronary artery disease (CAD). Methods: A total of 177 CAD patients were assessed for Type D personality. Plasma biomarkers of inflammation (TNF-α, IL-6, hs-CRP) were measured and pooled into standardized sumscores. Tryptophan and kynurenine metabolites were measured, and the kynurenine/tryptophan ratio (KTR) calculated. Plaque vulnerability was measured in vivo by optical coherence tomography. All patients had a follow up of two years in which cardiovascular adverse events were recorded. Results: Type D individuals exhibited elevated TNF-a (p = 0.007), IL-6 (p = 0.049), inflammation sumscore (p = 0.002), kynurenine (p = 0.008), and KTR (p = 0.005) than non-Type D group. The serial-multiple mediation revealed that Type D personality had a direct positive effect on plaque vulnerability, including thin cap fibroatheroma (TCFA) (point estimate = 0.81; 95% CI = 0.09-1.53), macrophages (point estimate = 0.79; 95% CI = 0.05-1.51) and MACE (point estimate = 0.88, 95% CI = 0.08-1.70). In addition, the standardized inflammation sumscore and KTR were mediators of the relationship between Type D personality and TCFA, macrophages and MACE. Conclusions: These findings showed that pro-inflammatory biomarkers and KTR can mediate the relationship between Type D personality and adverse cardiovascular outcomes in CAD patients.